2018
DOI: 10.18388/abp.2018_2639
|View full text |Cite
|
Sign up to set email alerts
|

Circular and long non-coding RNAs and their role in ophthalmologic diseases

Abstract: Long non-coding RNAs are >200-nucleotide-long RNA molecules which lack or have limited protein-coding potential. They can regulate protein formation through several different mechanisms. Similarly, circular RNAs are reported to play a critical role in post-transcriptional gene regulation. Changes in the expression pattern of these molecules are known to underlie various diseases, including cancer, cardiovascular, neurological and immunological disorders (Rinn & Chang, 2012; Sun & Kraus, 2015). Recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 95 publications
0
27
0
Order By: Relevance
“…processes by targeting genes [6]. Long noncoding RNAs (ln-cRNAs) are >200 nucleotides in length that regulate transcription (cis or trans), the organization of nuclear domains, and RNA or protein formation through several different mechanisms [6,74,75]. Recently, noncoding RNAs have become a focus of glaucoma research, as shown in Table.1.…”
Section: Fibrosis Nrf2 and Tenon's Capsule Cellsmentioning
confidence: 99%
“…processes by targeting genes [6]. Long noncoding RNAs (ln-cRNAs) are >200 nucleotides in length that regulate transcription (cis or trans), the organization of nuclear domains, and RNA or protein formation through several different mechanisms [6,74,75]. Recently, noncoding RNAs have become a focus of glaucoma research, as shown in Table.1.…”
Section: Fibrosis Nrf2 and Tenon's Capsule Cellsmentioning
confidence: 99%
“…MiRNAs are abundantly present in biological fluids and are reliable diagnostic and predictive biomarkers (Weber et al, 2010). Long noncoding RNAs are >200 nucleotide-long RNA molecules that lack or have limited protein-coding potential but can regulate miRNAs or protein formation through several different mechanisms (Wawrzyniak et al, 2018). Recently, noncoding RNAs have become popular subjects of glaucoma research (Table 1), providing attractive opportunities to defend against oxidative stress and to identify novel biomarkers for the diagnosis and prognosis of glaucoma.…”
Section: Survey Methodologymentioning
confidence: 99%
“…MicroRNAs are a class of small noncoding RNAs (19-25 nucleotides) that regulate a wide range of cellular processes by repressing the transcription or translation of their target genes. lncRNAs are >200-nucleotidelong RNA molecules that lack or have limited proteincoding potential but can regulate transcription in cis or trans, the organization of nuclear domains, and RNA or protein formation through several different mechanisms [166,167]. Recently, noncoding RNAs became a hot topic in scientific research, even in ocular research, as shown in Table 2.…”
Section: Novel Strategies For Activating Nrf2mentioning
confidence: 99%